Transcriptional Analyses Identify Genes That Modulate Bovine Macrophage Response to Toxoplasma Infection and Immune Stimulation - Gossner, Anton; Hassan, Musa A. (Frontiers in Cellular and Infection Microbiology, 2020)
The obligate intracellular parasite, Toxoplasma gondii, is highly prevalent among livestock species. Although cattle are generally resistant to Toxoplasma strains circulating in Europe and North America, the underlying mechanisms are largely unknown. Here, we report that bovine bone marrow-derived macrophage (BMDM) pre-stimulated with interferon gamma (IFNγ) restricts intracellular Toxoplasma growth independently of nitric oxide. While Toxoplasma promoted the expression of genes associated with alternative macrophage activation and lipid metabolism, IFNγ abrogated parasite-induced transcriptional responses and promoted the expression of genes linked to the classical macrophage activation phenotype. Additionally, several chemokines, including CCL22, that are linked to parasite-induced activation of the Wnt/β-catenin signaling were highly expressed in Toxoplasma-exposed naïve BMDMs. A chemical Wnt/β-catenin signaling pathway antagonist (IWR-1-endo) significantly reduced intracellular parasite burden in naïve BMDMs, suggesting that Toxoplasma activates this pathway to evade bovine macrophage anti-parasitic responses. Congruently, intracellular burden of a mutant Toxoplasma strain (RHΔASP5) that does not secrete dense granule proteins into the host cell, which is an essential requirement for parasite-induced activation of the Wnt/β-catenin pathway, was significantly reduced in naïve BMDMs. However, both the Wnt/β-catenin antagonist and RHASPΔ5 did not abolish parasite burden differences in naïve and IFNγ-stimulated BMDMs. Finally, we observed that parasites infecting IFNγ-stimulated BMDMs largely express genes associated with the slow dividing bradyzoite stage. Overall, this study provides novel insights into bovine macrophage transcriptional response to Toxoplasma. It establishes a foundation for a mechanistic analysis IFNγ-induced bovine anti-Toxoplasma responses and the counteracting Toxoplasma survival strategies.